2021
DOI: 10.1128/jvi.01155-21
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain of Salmonid Alphavirus Nonstructural Protein 2 (nsP2) Is Essential and Sufficient To Block RIG-I Pathway Induction and Interferon-Mediated Antiviral Response

Abstract: Salmonid alphavirus (SAV) is an atypical alphavirus, which has a considerable impact on salmon and trout farms. Unlike other alphaviruses such as the chikungunya virus, SAV is transmitted without an arthropod vector, and does not cause cell shut-off during infection. The mechanisms by which SAV escapes the host immune system remain unknown. By studying the role of SAV proteins on the RIG-I signaling cascade, the first line of defense of the immune system during infection, we demonstrated that non-structural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…High levels of intracellular SAV3 virus may thus possibly block or suppress expression of antiviral responses in the RTgutGC cells. Both mammalian and fish alphaviruses including SAV have been described to suppress or evade host interferon responses to escape the innate immune system of the host [46] and this could be related to protein shutdown [24]. A comparative study of SAV2 infection in TO and SHK-1 cells showed higher expression of the interferon-induced gene mx in SHK-1 cells concomitant with a lesser ability to induce CPE compared to TO cells, indicating that the ability of the virus to interfere with the cell's interferon signaling pathway is important for intracellular SAV replication and the ability to induce cytopathogenicity [43].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of intracellular SAV3 virus may thus possibly block or suppress expression of antiviral responses in the RTgutGC cells. Both mammalian and fish alphaviruses including SAV have been described to suppress or evade host interferon responses to escape the innate immune system of the host [46] and this could be related to protein shutdown [24]. A comparative study of SAV2 infection in TO and SHK-1 cells showed higher expression of the interferon-induced gene mx in SHK-1 cells concomitant with a lesser ability to induce CPE compared to TO cells, indicating that the ability of the virus to interfere with the cell's interferon signaling pathway is important for intracellular SAV replication and the ability to induce cytopathogenicity [43].…”
Section: Discussionmentioning
confidence: 99%